2016
DOI: 10.1038/srep30544
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, body composition and lipids changes in adolescents: analysis from the MyHeART Study

Abstract: Insufficient physical activity and growing obesity levels among Malaysian adolescents are becoming a public health concern. Our study is to identify the trends of self-reported physical activity (PA) levels, blood lipid profiles, and body composition (BC) indices from a cohort of 820 adolescents. The self-reported PA was assessed using a validated Malay version of the PA Questionnaire for Older Children (PAQ-C). Fasting blood samples were collected to investigate their lipid profiles. Height, weight, waist and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 34 publications
(46 reference statements)
2
22
2
Order By: Relevance
“…The paper presents mathematical models for the prediction of VO 2 max based on a 20 m SRT and anthropometric parameters. All models were developed and cross-validated using a sample of 308 healthy young people (aged [19][20][21][22][23][24][25][26][27]. The models obtained are classified as "maximal models" [49] and that is why errors in this group of models were compared with errors presented by other authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper presents mathematical models for the prediction of VO 2 max based on a 20 m SRT and anthropometric parameters. All models were developed and cross-validated using a sample of 308 healthy young people (aged [19][20][21][22][23][24][25][26][27]. The models obtained are classified as "maximal models" [49] and that is why errors in this group of models were compared with errors presented by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…A higher physical fitness index in adults significantly reduces the metabolic risk for a particular body fat level [17]. Preventive measures against cardiovascular diseases which are intended to optimise CRF are also implemented in low-risk groups (10% risk of ischaemic heart disease occcurrence within the next 10 years) [18][19][20]. The authors of many studies emphasise the significance of lifelong physical activity to improve or maintain the appropriate level of CRF [19,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study by Majid et al carried out in Malaysian adolescents aged from 13 to 15 years old indicated a gender gap between physical activity levels and body composition and, accordingly, blood lipids [13]; Therefore, it is important to take into account of different types of physical activities and the gender gap when assessing its association with the prevalence of dyslipidemia. In the current study, we investigated physical activities and sedentary behaviors in different domains in primary school children, and assessed their association with physical fitness and the prevalence of dyslipidemia, stratified by gender.…”
Section: Introductionmentioning
confidence: 99%
“…The protective effect of PA on adiposity parameters represents an opportunity for early intervention in adolescents, in view of the high prevalence of obesity in this country ( 1 ). Of concern, significant downward trends of PA were shown in Malaysian girls in the 2-year follow-up of the same cohort accompanied by concurrent % BF increment ( 29 ). Thus, effective policies to promote PA in this age group are warranted with interventions to be planned at all levels of the community ( 30 ).…”
Section: Discussionmentioning
confidence: 96%